Areas for Student Participation and the Rights Perspective in Secondary Schools (Itinerarios Educativos, 2020)
This paper presents partial results of aresearch project aimed at studying the constructionof the rights perspective in three secondary schoolsdealing with social inequality contexts in an intermediate city of the province of Córdoba. The present workaddresses the senses conveyed by youngsters in relationto the practices institutionalized by schools as rightsenhancers in the dynamic and complex process of constructing citizenship within a context of neoconservative re-emergence that dispute over senses about the rightsperspective in schools. The practices of youngsters instudent councils of three schools and the areas forschool assemblies are analyzed so as to question howthey strengthen and/or put a strain on the rights perspective taken on for institutional projects.
Keywords: Rights; youngsters; citizenship; schools